ChemInform Abstract: Palladium‐Catalyzed Mono‐α‐arylation of Carbonyl‐Containing Compounds with Aryl Halides Using DalPhos Ligands. Issue 15 (25th March 2013) - Crawford, Sarah M.; Alsabeh, Pamela G.; Stradiotto, Mark
Abstract Aryl methyl ketones, heteroaryl methyl ketones, propiophenones, malonates, and methoxyacetone can be α‐arylated with aryl halides or heteroaryl halides under relatively mild conditions.